A Glanzmann’s Thrombasthenia Cluster Among Iraqi Jews in Israel - Seligsohn, U; Rososhansky, S (Thrombosis and Haemostasis, 1984)
A country-wide survey of Glanzmann’s thrombasthenia in Israel identified 44 patients. The patients belong to 23 unrelated families, 17 of whom are of Iraqi Jewish origin. The frequency of thrombasthenia among Iraqi Jews in Israel (total population 270,000) is 1:7714 and thus the calculated frequency of the carrier state is 2.3%.
Keywords: Thrombasthenia; Glanzmann’s thrombasthenia; Platelet disorders